Pengaruh Organizational Citizenship Behavior Dan Workload Terhadap Job Satisfaction Di Gran Melia Jakarta - Muhammad Rizky Fitrian; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
In the scope of the workplace, job satisfaction plays a significant role, believed to influence both Organizational Citizenship Behavior (OCB) and workload levels. The study adopts a quantitative approach with a causal associative method, involving the entire population of 97 employees through total sampling technique. Data collection is conducted using a structured questionnaire that utilizes the Likert scale to ensure the validity and reliability of the instrument. Data analysis is performed using SPSS software version 25.00, which yields an R-square value of 0.345 for the job satisfaction variable. Hypothesis testing supports the positive influence of organizational citizenship behavior on job satisfaction (with a t-statistic value of 2.773 > 1.96) and the positive impact of workload levels on job satisfaction (with a t-statistic value of 6.187 > 1.96).